PENDAPATAN PETANI JAGUNG ANGGOTA DAN NONANGGOTA KOPERASI TANI MAKMUR DESA NATAR KABUPATEN LAMPUNG SELATAN - Ariansah Saputra Dinata; Dyah Aring Hepiana Lestari; Helvi Yanfika (Lampung University, 2014)
The purposes of this research are to compare the corn farmer’s income between Tani Makmur Cooperative’s member and non member in Natar District Lampung Selatan and knowing the impact of cooperative membership for corn farmer who is member of Tani Makmur cooperative in Natar District South Lampung Regency. This research was taken place in Natar village from Juni 2013 to September 2013. The total of respondents are 48 corn farmers, consisting of 24 farmer members and 24 farmers not members of Tani Makmur Cooperative. They are chosen by using Simple Random Sampling Technique. Data used include primary and secondary data. Primary data are obtained by interviewing respondents using questionnaires. Secondary data are obtained from various literatures, printed media and some related agencies. The results of statistical analysis showed that there is a significant differentiation of corn farmer’s income between Tani Makmur Cooperative’s Members and Non Members in Natar Districk South Lampung Regency. The average income in first season of cooperative member (Rp8,257,396.09) was larger than the average income of corn farmer non cooperative member (Rp7,728,231.10). In the second season, the average income of corn farmer cooperative member also larger (Rp4,749,114.97) than the average income of corn farmer non cooperative members (Rp4,448,974.41). The number of Cooperative economic benefits for members of the cooperative was Rp1,450,000.00 and the number of accounted benefits was Rp9,210,000.00 which derived from the difference price of production means such as Phonska fertilizer, urea fertilizer, and SP-36 fertilizer. The average number of cooperative economic benefits for total household income was Rp60,416.67, or 0.003 percent of the total household income per year cooperative member farmers. Keywords: benefit, comparing, cooperative, corn, income